Analisis transformasi manajemen website untuk meningkatkan daya saing di era digital - Marsis, Yoki; Amir, Muhammad Taufiq (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted with the aim of finding out how the management of news websites within conventional television media companies carries out the transformation process to increase competitiveness in the digital era. The focus of this research problem is on changes made by the management of the tvOnenews.com website as a website that focuses on news and sports within the tvOne company to increase competitiveness in the digital era. The theories used in this research are Kotter's change management model, Grundy's types of change, Kreitner and Kinicki's organizational change factors, Holt et al.'s change readiness, Robbins and Coulter's organizational structure, John's organizational types, and Osterwalder et al.'s value proposition canvas to see the management transformation that has occurred due to digitalization and the rapid development of technology. The research paradigm used is postpositivism with a qualitative approach. The research results were obtained using interview and observation techniques with the research subjects, namely tvOne and tvOnenews.com management, who were directly involved in the process of increasing website competitiveness, as well as other data from reliable sources. The results and analysis of the research show the transformation that occurs in the management of tvOnenews.com by increasing competitiveness in the digital era.